2006
DOI: 10.1007/s00414-005-0073-7
|View full text |Cite
|
Sign up to set email alerts
|

Gunshot-related transport of micro-organisms from the skin of the entrance region into the bullet path

Abstract: The skin defect of a gunshot entrance wound is caused by the retrograde and anterograde displacement of skin particles. In the present study, we investigated whether gunshots to bacterially contaminated skin are associated with the transport of micro-organisms into the bullet path. The shots were fired into composite models of pig skin and gelatin blocks. The outer surface of the skin was covered with a thin layer of a defined bacterial suspension [green fluorescent protein-labelled Escherichia coli in the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 21 publications
1
24
0
Order By: Relevance
“…Nine pieces of pig skin, each measuring 25×10 cm, were stained in a haematoxylin bath, dried and disinfected as described in a previous study [6]. Directly before the test shots, 1 ml of a bacterial suspension (S. epidermidis, DSM 1798, 10 8 CFU/ml) was applied to the skin surface (Fig.…”
Section: Main Test Series With Staphylococcus Epidermidismentioning
confidence: 99%
See 2 more Smart Citations
“…Nine pieces of pig skin, each measuring 25×10 cm, were stained in a haematoxylin bath, dried and disinfected as described in a previous study [6]. Directly before the test shots, 1 ml of a bacterial suspension (S. epidermidis, DSM 1798, 10 8 CFU/ml) was applied to the skin surface (Fig.…”
Section: Main Test Series With Staphylococcus Epidermidismentioning
confidence: 99%
“…On the other hand, the gunshot entrance wound is typically characterised by a skin defect that could be shown to be caused by anterograde and retrograde displacement of macroscopically visible and microscopically small skin particles [5]. Furthermore, it has been demonstrated that microorganisms from the skin of the entrance site are carried along the whole length of the bullet track and may therefore constitute a source of infection in gunshot victims [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For each group (a cotton, b jeans, c leather, d nylon) and firing distance tested (5,15, and 30 cm), the macroscopic features of the fabrics and the underlying skin and the micro-CT reconstructions (frontal and lateral views) of the wounds are represented particular, it was assumed that the density of textile fibers in the bullet entrance was higher than that in the exit site. This general rule, however, has been recently questioned by Vennemann et al [26] in an experimental study performed on a porcine skin-gelatine model [27,28]. The authors observed a retrograde displacement of fibers from the clothing back into the bullet path.…”
Section: Discussionmentioning
confidence: 87%
“…The principal technical procedure has already been described in previous papers [4,7,20,21]. In order to imitate a reentry shot constellation, two cylindrical gelatine blocks (24×8 cm in size) were tightly wrapped in pieces of skin from the belly region of slaughtered pigs and arranged one behind the other by means of a metal rack which permitted the distance between the cylindrical segments to be varied (Fig.…”
Section: Methodsmentioning
confidence: 99%